Pandangan Alkitabiah Terhadapa Penderitaan Dalam Konteks Indonesia - Filiani Filiani; Aprianus Lendrik Moimau (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
In the beginning God created humans and hoped that humans could reflect life as God's glorious creation, that is, in the image and similarity of God. For Irenius, the image of God meant â€œHuman nature as a rational and free being. In connection with the term "image and likeness to God," Lempp writes that: "Man is the goal and crown of all creatures, outwardly and inwardly created by God, according to God, of the same character, talent, character, character with God, and all are imitated according to the original. .â€